Transforming Halal Training Through Gamification and Immersive Technology to Empower Talents - Adlin Masood; Nur Aqilah Hazirah Mohd Anim; Anita Ismail (Universiti Sains Islam Malaysia, 2024)
The Journal of Muamalat and Islamic Finance Research, Volume 21 Issue 1 Page (70-81)